Unraveling the Effects of Biochemical Drivers on the Bacterial Communities and Volatile Profiles in Refrigerated Sturgeon Filets at 4°C - Tan, Chunming; Xiao, Mengyuan; Wu, Ruiyun; Li, Pinglan; Shang, Nan (Frontiers in Microbiology, 2022)
Spoilage bacteria seriously influence the flavor and quality of fish meat. In this study, we investigated the quality characteristics, bacterial community, and volatile profiles of the refrigerated (4 °C) sturgeon fillets during 10-day storage. Refrigerated samples on day 10 showed the lowest bacterial diversity and the largest difference in microbiota and biochemistry. The dominant genera in the fresh samples were Macrococcus, Acinetobacter, Moraxella, Brucella, and Pseudomonas, while the dominant bacteria changed into Acinetobacter, Carnobacterium, Macrococcus, Pseudomonas, and Psychrobacter at the end of storage. Our results suggest that these dominant taxa contribute to the spoilage of the refrigerated sturgeon fillets. Meanwhile, during the storage, total viable counts (TVC), total volatile basic nitrogen (TVB-N), thiobarbituric acid reactive substances (TBARS), and trichloroacetic acid (TCA)-soluble peptide significantly increased (P<0.05), while sensory score decreased steadily. Additionally, ATP-related compounds and K-value showed similar increasing trends. The shelf-life of refrigerated sturgeon fillets was less than 8 days. GC-IMS results suggest that hexanal, ethyl acetate, ethanol, butanal, 1-propanol, isopentyl alcohol, 2-pentanone, 2-heptanone, ethyl propanoate, and propyl sulfide are potential chemical spoilage markers. The predicted metabolic pathways indicated an abundant carbohydrate metabolism and amino metabolism in the refrigerated sturgeon fillets. This study provides insight into the determinants of sturgeon shelf life and the its spoilage process involved in refrigerated fish.